2022
DOI: 10.3389/fpls.2022.972481
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association for heat tolerance at seedling stage in historical spring wheat cultivars

Abstract: Increasing global temperature has adverse effects on crop health and productivity at both seedling and reproductivity stages. It is paramount to develop heat tolerant wheat cultivars able to sustain under high and fluctuating temperature conditions. An experiment was conducted to characterize 194 historical wheat cultivars of Pakistan under high temperature at seedling stage to identify loci associated with heat tolerance using genome-wide association studies (GWAS). A quantitative trait locus, TaHST1, on chr4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…QHST3 on Chr1D was found to associated with traits such as TRL-HS, MRL-HS, HSI-TRL, and HSI-MRL, which was also identified in previous research (Table 3 ) [ 1 ]. Two QTLs, QSRHS.nri-2 A and QSLHR.nri-7D , previously found at the seedling stage [ 36 ], were also detected in this study shown as QHST4 and QHST5 (Table 3 ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…QHST3 on Chr1D was found to associated with traits such as TRL-HS, MRL-HS, HSI-TRL, and HSI-MRL, which was also identified in previous research (Table 3 ) [ 1 ]. Two QTLs, QSRHS.nri-2 A and QSLHR.nri-7D , previously found at the seedling stage [ 36 ], were also detected in this study shown as QHST4 and QHST5 (Table 3 ).…”
Section: Discussionsupporting
confidence: 79%
“…The heat susceptible index (HSI) is widely used to evaluate HST for wheat [ 1 , 37 ]. The wheat varieties were considered to be high heat-resistance materials if HSI were less than 0.5 [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present work is also distinct from much of the above published works, as it concerns heat stress exposure and thermotolerance at an early developmental stage. The study of the genetic governance of wheat seedling thermotolerance is fairly limited, with only a handful of published works identifying key genes or genomic regions associated with the trait (Abd El‐Daim et al., 2014 ; Khan et al., 2022 ; Khatun et al., 2018 ). Much of the study on the effect of heat stress on wheat concerns its effect at, or around, anthesis and grain filling, and its subsequent effect on yield, as these are the developmental stages when heat stress commonly occurs in some major wheat producing countries (Stone & Nicolas, 1994 , 1995 , 1996 ).…”
Section: Discussionmentioning
confidence: 99%